2021
DOI: 10.1021/acsestengg.1c00110
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and Emerging Water Disinfection Technologies Challenging the Control of Antibiotic-Resistant Bacteria and Antibiotic Resistance Genes

Abstract: The emergence of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in the environment has created obstacles when treating infectious diseases with antibiotics. Wastewater treatment plants (WWTPs) serve as reservoirs for ARB and ARGs and can disseminate them into the environment. It is important to understand and address these risks. Generally, professional disinfection processes have been used in WWTPs to disinfect the target water body, with the goal of eliminating pathogenic microorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 194 publications
0
31
0
Order By: Relevance
“…Compared with the undamaged bacteria, the surfaces of damaged bacteria were torn or wrinkled (SI Figure S24) due to the destruction of cell membrane. ClO 2 inactivates bacteria by increasing the permeability of cell membranes and leaking intracellular enzyme outside the cell . Previous studies showed that DNA transformation of microrganism was not affected by ClO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the undamaged bacteria, the surfaces of damaged bacteria were torn or wrinkled (SI Figure S24) due to the destruction of cell membrane. ClO 2 inactivates bacteria by increasing the permeability of cell membranes and leaking intracellular enzyme outside the cell . Previous studies showed that DNA transformation of microrganism was not affected by ClO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we coupled vis-photocatalysis with chlorite activation (vis/chlorite) where ClO 2 – would be activated by photoinduced •OH to produce chlorine dioxide (ClO 2 ), promoting the norfloxacin degradation rate by 7.3 times over the vis-photocatalytic process alone . Moreover, ClO 2 not only improves degradation efficiency and eliminates biotoxicity by selectively attacking electron-donating groups in contaminant molecules, but also serves as a popular disinfectant to control water-borne pathogens . Based on the chlorite activation process, the vis/chlorite technique can simultaneously meet the needs of pollutant degradation and pathogen inactivation, emerging as a promising technique in water purification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, extravagant disinfection was found to be the villain of microbial resistance (Lu and Guo, 2021). Under disinfection, transforms of physiological state, e.g., increasing membrane permeability, SOS response and stress response offered an easier access for microorganisms to resistance ( Cai et al, 2021 ). Equipped with horizontal transfer, viruses served as antibiotic resistance gene pool ( Debroas and Siguret, 2019 ).…”
Section: Succession Of Virus Community Initiated By Covid-19 Preventi...mentioning
confidence: 99%
“…Residues are constantly released into the environment, aiding in the spread of resistance genes among bacteria. This endangers both human health and the stability of the ecosystem (Cai et al 2021). As a result, there is an urgent need to develop suitable methods for degrading TC.…”
Section: Introductionmentioning
confidence: 99%